Biotechcnological Method To Prevent Erosion - Sinniah, Loges (Universiti Sains Malaysia, 2005)
Biotechnology method is one of the applications in engineering methods where it was using the mechanical element and combination with biological element, mainly live staking plant for the reason of slope stability, soil stability and erosion control. The methods for research using here were coconut fiber and oil palm fiber with live staking plant. Research for study how effective these methods were done. The direct shear test give the results where coconut fiber is more effective compare with oil palm fiber. It has the highest fastening with the long coarse grass compare with grass where long coarse grass have strand root and straight root. The root will go through the fiber and inside the soil so the soil become more stabilize than before.